Fuzzy Logic Control System for Maximum Power Output of Wind Turbines - I Made Mataram (Journal of Electrical, Electronics and Informatics, 2025)
This study discusses the application of fuzzy logic control systems for maximum power point tracking (MPPT) in wind turbines, focusing on the system's performance. Fuzzy logic control is used to optimize the operation of wind turbines by adjusting the turbine's rotational speed based on input variables such as wind speed and torque, which are often difficult to model mathematically with high accuracy. By employing a fuzzy approach, the system can handle uncertainties and nonlinearities in the wind turbine's operational environment, thus providing more adaptive and responsive control to changes in wind conditions. Experimental results show that the fuzzy control system can improve the power output efficiency of wind turbines by maximizing the generated power under varying wind speeds. The system's performance is evaluated based on parameters such as power output stability, response time, and accuracy in reaching the maximum power point. Simulation and experimental results reveal that the fuzzy control approach offers superior performance compared to traditional control methods, making it an effective alternative for optimal wind turbine operation.